Web-based design and development of an e-Research Information System for the Muhammadiyah Cileungsi College of Technology using the Agile method - Mohamad Anas Sobarnas; Nanik Wuryani; Mustopa Idris; Faiz Abdillah (INFOTECH : Jurnal Informatika & Teknologi, 2024)
Research and community service (PkM) are higher education principles that must be carried out by lecturers. Managing these activities requires good management, because each period is used by lecturers to fill in lecturer data and the campus in carrying out higher education clustering assessments. To simplify the process of managing data, submissions and activity history, an application is needed to support this process. The aim of this research is how to design an e-research information system application at the Muhammadiyah Cileungsi College of Technology based on a website using agile methods with the C# .Net programming language and SQL Server database. The application was built with the aim of simplifying the process of submission, approval, activity monitoring, reports and activity history. The application is designed to be website-based with consideration of ease of access for all users. Based on user satisfaction of 82% very good and 18% good, the application is felt to be useful and suitable for use